2020
DOI: 10.3390/toxins12010048
|View full text |Cite
|
Sign up to set email alerts
|

Role of Shiga Toxins in Cytotoxicity and Immunomodulatory Effects of Escherichia coli O157:H7 during Host-Bacterial Interactions in vitro

Abstract: Enterohemorrhagic Escherichia coli (EHEC) strains are food-borne pathogens that can cause different clinical conditions. Shiga toxin 2a and/or 2c (Stx2)-producing E. coli O157:H7 is the serotype most frequently associated with severe human disease. In this work we analyzed the hypothesis that host cells participate in Stx2 production, cell damage, and inflammation during EHEC infection. With this aim, macrophage-differentiated THP-1 cells and the intestinal epithelial cell line HCT-8 were incubated with E. col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The experimental results indicated that the vgrG2 gene may participate in the immune evasion of BPM and play a key role in the evasion of innate immune responses in whole blood. Bacterial adherence to and interaction with RAW264.7 cells are prerequisites for the induction of bacterial infection ( Bruballa et al, 2020 ). We observed the invasion and survival abilities of the BPM, mutant and complemented strains and compared them to the abilities of RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental results indicated that the vgrG2 gene may participate in the immune evasion of BPM and play a key role in the evasion of innate immune responses in whole blood. Bacterial adherence to and interaction with RAW264.7 cells are prerequisites for the induction of bacterial infection ( Bruballa et al, 2020 ). We observed the invasion and survival abilities of the BPM, mutant and complemented strains and compared them to the abilities of RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bilophila and Phascolarctobacterium promote pro-inflammatory cytokines associated with innate immune cells while maintaining Th1/Th2 and Treg/Th17 balance to some extent [ 120 , 121 , 122 , 123 , 124 , 125 ]. Other bacteria in this group display a more complex and indeterminate association with inflammation [ 51 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 ]. Escherichia is [ 128 , 129 ] uncertainly associated with IgE production while Prevotella mainly promotes inflammation, but exhibits a negative association with production of IgE [ 131 , 132 ].…”
Section: The Association Between Changed Bacteria and Immune Disordersmentioning
confidence: 99%
“…[120][121][122][123][124][125] Other bacteria in this group display more complex and uncertain relationships with inflammation. 51,[126][127][128][129][130][131][132][133][134][135][136] Escherichia is uncertainly connected with IgE. 128,129 Prevotella mainly promotes inflammation, but negatively related with IgE.…”
Section: The Association Between Changed Microbiota and Immune Disordersmentioning
confidence: 99%